Carrageenan as an Ecological Alternative of Polyvinylidene Difluoride Binder for Li-S Batteries - Kazda, Tomáš; Capková, Dominika; Jaššo, Kamil; Fedorková Straková, Andrea; Shembel, Elena; Markevich, Alex; Sedlaříková, Marie (Materials (Basel, Switzerland), 2021)
Lithium-sulfur batteries are one of the most promising battery systems nowadays. However, this system is still not suitable for practical application because of the number of shortcomings that limit its cycle life. One of the main problems related to this system is the volumetric change during cycling. This deficiency can be compensated by using the appropriate binder. In this article, we present the influence of a water-soluble binder carrageenan on the electrochemical properties of the Li-S battery. The electrode with a carrageenan binder provides good stability during cycling and at high C-rates. Electrochemical testing was also carried out with a small prototype pouch cell with a capacity of 16 mAh. This prototype pouch cell with the water-based carrageenan binder showed lower self-discharge and low capacity drop. Capacity decreased by 7% after 70 cycles.
Keywords: carrageenan; binder; sulfur; Li-S battery; lithium; battery; cathode; pouch cell